PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) DILENGKAPI MEDIA REALIA UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR BIOLOGI - Setiyarini, Eka (UNIVERSITAS MUHAMMADIYAH METRO, 2013)
Based on result of observed in VII grades of SMP Negeri 2 Tegineneng, in learning process students participant is low so learning process is not active. Thatâs conditions make the result of biological studies was low. The purpose of this research is to improve activity studies and the result of biological studies using the Cooperative learning of think pair share method with a realia media in VII grades of SMP Negeri 2 Tegineneng, amounting to 30 students. This study is a Classroom Action Research (PTK) with two cycle each consisting of three sessions. Activity of studies has incrased from cycle I to cycle II. 16.67% for attendtioning of teacher, 14,99% for thingking the work papper, 18,32% for pairing on discuss, and 19,99% for sharing the result of discuss on class. Data on studentsâ cycle I into cycle II incrased of 13,34% was passing the exam. From the result of these studies suggest that the teacher to apply these method in teaching science, especially biology.Kata kunci: Think pair share, media realia, aktivitas dan hasil belajar biologi